Form of Discrimination against Female Characters with Autism Spectrum Disorder in Korean Drama Series Extraordinary Attorney Woo: Qualitative Content Analysis of The Character Woo Young Woo In The Drama Series Extraordinary Attorney Woo - Naurissa Biasini; Dita Azelia Subarman (Universitas Multimedia Nusantara, 2023)
The drama series Extraordinary Attorney Woo is a Korean drama that portrays the life of a lawyer with an autism spectrum disorder. This drama series has sparked controversy among the public due to its portrayal of individuals with autism being deemed unrealistic. Discrimination occurs because society perceives individuals with autism as needing care and being deemed useless in society. These forms of discrimination are analyzed based on the Villines discrimination model, which consists of hostile ableism, benevolent ableism, and ambivalent ableism. This research aims to understand the forms of discrimination against female characters with autism spectrum disorder in the drama series. This research adopts a post-positivist paradigm with a qualitative approach. The results of this study show that almost three-quarters of the total episodes depict various forms of discrimination, including hostile ableism, benevolent ableism, and ambivalent ableism. These findings align with the director Yoo In Shik's intention in creating the extraordinary attorney woo drama series, which is to portray the societal reality towards individuals with autism spectrum disorder, who are considered in need of care or even deemed useless in society. These findings imply that the depicted forms of discrimination are the director's efforts to provide understanding to the public regarding the existence of discrimination against individuals with autism spectrum disorder within the context of the main character's profession as a lawyer.